Continuous-Flow Phosphate Removal Using Cry-Ca-COS Monolith: Insights from Dynamic Adsorption Modeling - Chanadda Phawachalotorn; Worawit Wongniramaikul; Satabodee Kaewnoo; Aree Choodum (My University, 2024)
This study rigorously evaluates the adsorption performance of the Cry-Ca-COS monolith for phosphate removal in a column operation mode. Characterization of the material both before and after exhaustion in a continuous flow system (column form) showed no difference compared to results from a batch system (tablet form). The XPS results indicated that the adsorption mechanism of phosphate on the Cry-Ca-COS column involved surface microprecipitation and ligand exchange (inner-sphere complexation). A systematic examination of key parameters revealed that higher column height, lower flow rate, and higher initial phosphate concentration favor increased phosphate adsorption in continuous mode. The application of the developed system to a real wastewater sample resulted in a satisfactory removal efficiency of 99.16 %, along with a concurrent reduction in total suspended solids (TSS) by 63.07 %. The adsorption data were analyzed using five dynamic adsorption models-Adam-Bohart, Wolborska, Thomas, Yoon-Nelson, and Yan-employing both linear and non-linear approaches. The non-linear models demonstrated a better fit with the experimental data, as indicated by higher correlation coefficients (R² = 0.9994 in the Yoon-Nelson model). An analysis of comprehensive errors was also conducted to assess the adequacy and precision of the model equations.
Keywords: Monolith; Phosphorus and nutrient management